2005
DOI: 10.1128/jvi.79.23.14526-14535.2005
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Rotavirus with Human Myeloid Dendritic Cells

Abstract: Rotaviruses (RV) are responsible for the deaths of approximately 1,200 children daily worldwide (41). To develop new strategies for treating or preventing this disease, our laboratory is currently characterizing human virus-specific T and B cells in children and adults (16,23,24,48). We recently showed that healthy adults have very low frequencies of circulating CD4 ϩ and CD8ϩ RV-specific T cells that secrete gamma interferon (IFN-␥) (23, 48). Significantly higher frequencies of these cells were found in sympt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
37
1
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 57 publications
9
37
1
4
Order By: Relevance
“…Although their rarity precludes further experimental marker delineation, their variable CD4, CD8 and CD11b expression suggests that RRV associates with several cell subsets. A similar pattern of infectious rotavirus association with multiple subsets of APC occurs in diabetes-resistant mouse strains and human mononuclear cells [22,38,39]. The uptake of infectious rotavirus by CD3 −…”
Section: Discussionmentioning
confidence: 82%
“…Although their rarity precludes further experimental marker delineation, their variable CD4, CD8 and CD11b expression suggests that RRV associates with several cell subsets. A similar pattern of infectious rotavirus association with multiple subsets of APC occurs in diabetes-resistant mouse strains and human mononuclear cells [22,38,39]. The uptake of infectious rotavirus by CD3 −…”
Section: Discussionmentioning
confidence: 82%
“…The vaccine strain RRV (G3 P [3]) and human virus Wa (G1 P1A [8]) were used to infect circulating and intestinal human B cells. Viruses were produced in MA104 cells as previously described (26,52), with minor modifications. Briefly, a semiconfluent monolayer of MA104 cells was washed three times with serum-free medium and infected at a multiplicity of infection (MOI) of 10 during 1 h at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…To produce mock-infected cells, the same process was performed without virus. The titer of the virus was determined with MA104 cells as previously described (52).…”
Section: Methodsmentioning
confidence: 99%
“…This assay allows quantitation of HRV-specific IFN-γ producing T cells, at the single cell level [29]. Studies of the interaction of rotavirus with human myeloid dendritic cells (MDCs) demonstrated that intact peripheral blood mononuclear cell (PMNC) populations containing antigen presenting cells are equally efficient compared to rotavirus-infected MDC, in stimulating IFN-γ-producing rotavirus-specific effector-memory T cells [30]. Furthermore, the frequencies and patterns of cytokines produced by effector-memory CD4+ T cells after stimulation of peripheral blood MNC with the purified rhesus rotavirus (RRV) or MDC infected with RRV were similar.…”
Section: Introductionmentioning
confidence: 99%